Frühes Christentum «An der (Ost) Grenze» Europas - Pillinger, R. (Боспорские исследования, 2010)
This article seeks to demonstrate the significance of early Christianity as a typical boarder region where there is Ukraine today. Special attention is paid to the monuments from Chersonesos in Sevastopol and from Panticapaion in Kerch. Consideration is also given to this region as a place of banishment. Эта статья призвана продемонстрировать значимость раннего христианства для такого приграничного региона, как территория современной Украины. Особое внимание уделено памятникам Херсонеса в Севастополе и Пантикапея в Керчи. Уделено внимание этому региону как месту изгнания. Ця стаття покликана продемонструвати значимість раннього християнства для такого прикордонного регіону, як територія сучасної України. Особлива увага приділяється пам’яткам у Севастополі і Пантікапею у Керчі. Також приділяється увага цьому регіону як місцю вигнання.